Política de desenvolvimento portuário brasileiro: uma abordagem multidimensional do período 1993-2013 - Galvão, Cassia Bömer (2017)
The objective of this research was to identify how the Brazilian port development did took place in the 1993-2013 period. Thus, the research aimed to characterize the changes in the Brazilian port development policy during the FHC, Lula and Dilma governments. In the context of the world economy, there were evidences of increasing volume and speed of seaborne trade of merchandise goods. In the case of Brazil, during the analyzed period, it was identified, that besides the significant increase in the volume of merchandise, there were institutional and regulatory changes that took place under the process of “port reform”. Thus, based on a multimethod analysis, the Brazilian port policy was approached in three dimensions. First, the economic dimension has studied the relations between economic and port development. The second, dealt with the strategic dimension, having as parameters of analysis the key variables in the strategic determination of the ports, such as planning and the investments. Finally, the third dimension was devoted to the political aspects, seeking the identification of actors and interest groups, as well as their correlations of political forces that resulted in the organizational and regulatory changes of the sector in two different moments that were verifiable in the passing of Law 8630 in 1993 and Law12815 in 2013. The results of the analysis showed that the Brazilian port policy was directly influenced by the changes of political economy context characterized by the State performance and its bloc in power. The analysis presented here is critic as it deals with port development as a result of the interaction of the economic, strategic and political dimensions and not as a natural evolution of free market forces